Higher Education Teachers Digital Literacy Competencies Exploration of Cultivation Models - Based on New Liberal Arts Contextual Perspectives - Yang, Yong; Yang, Mengling; Zheng, Zongying (International Journal of Scientific Research and Management (IJSRM), 2024)
In the context of the new liberal arts, teachers' digital literacy ability has become a key factor affecting the effectiveness of education. At present, some colleges and universities are still facing a lot of problems in cultivating teachers' digital literacy ability, which are mainly manifested in the low utilization rate of digital teaching resources, imperfect teaching digital evaluation system, lack of personalized and systematic cultivation of teachers' digital literacy ability, and teachers' cross-fusion ability of disciplines need to be strengthened and so on. In view of these difficulties encountered in the cultivation of teachers' digital literacy, three new cultivation modes are proposed, namely, the implementation of the "cloud platform" cultivation mode, the establishment of the "research-practice-competition" integrated cultivation mode, and the promotion of the "research-practice-competition" integrated cultivation mode. Three new cultivation modes are proposed, namely the implementation of the "cloud platform" cultivation mode, the establishment of the "research-practice-competition" integration cultivation mode, and the promotion of the "market mechanism" cultivation mode, and we hope to provide reliable suggestions for the cultivation of the digital literacy competence of college teachers in China.